Pengembangan ketrampilan pembuatan laporan keuangan sederhana dengan Microsoft Excel di SMK Negeri 2 Denpasar - Fredlina, Ketut Queena; Dewi, Putri Anugrah Cahya; Astawa, Ni Luh Putu Ning Septyarini Putri; Juliharta, I Gede Putu Krisna (Penamas: Journal of Community Service, 2024)
In an era of rapid industrial and business transformation, SMK N 2 Denpasar recognizes the urgent need for strong administrative skills. Acknowledging the importance of financial report preparation skills, training using Microsoft Excel becomes a strategic step. This training aims to enhance students' technical skills and provide an understanding of the basic concepts of financial reporting and its importance in decision-making. Approximately 80 participants from the Accounting and Financial Institutions, Online Business and Marketing, Banking and Microfinance, and Office Management departments attended the training. The results of the training showed a significant increase in students' understanding of financial report preparation and analysis. Students were able to use Microsoft Excel more effectively to create simple financial reports, analyze data, and interpret the results. The simulated projects reinforced their technical skills and boosted their confidence. Post-training evaluations indicated that participants felt more prepared and confident in managing financial data independently. Students successfully applied the skills they learned to create simple financial reports effectively.